On Designing Interactive Online Atlas of Reptile Anatomy (Mabouya multifacsiata) - Muhammad Jafar Luthfi; Riyanto Riyanto (Biology, Medicine, & Natural Product Chemistry, 2017)
This research is an integration between fields of Biology, Photography, Design, and Informatics Engineering. The study aimed to build an interactive online atlas of reptile anatomy to improve the accessibility and data sharing (free access) of reptile anatomy. Website was developed using SDLC (System Development Life Cycle) which consist of five steps as follows: website’s strategic planning, determine the scope of website, website’s requirements analysis, design and implementations of website, and testing. Based on the results of testing and system implementation, it can be concluded that online interactive atlas (AtlasAnatomy.org) had been successfully built as anatomical educational media of reptile.